Advances in the study methods of cerebral venous sinus hemodynamics - ZHANG Jia‐hao; GENG Lei; XIAO Zhi‐tao; CHEN Xing; CAO Xiang‐yu (Chinese Journal of Contemporary Neurology and Neurosurgery, 2025)
Cerebral venous system diseases can lead to idiopathic intracranial hypertension (IIH), cerebral venous thrombosis (CVT) and pulsatile tinnitus (PT), and accurate evaluation of cerebral venous sinus hemodynamics is very important for the diagnosis and treatment of these diseases. In recent years, with the rapid development of hemodynamics research software and brain imaging technology, computational fluid dynamics (CFD), 4D Flow MRI, vitro simulation and transcranial Doppler ultrasonography (TCD) provide a multi-dimensional tool for the study of hemodynamics. In this paper, we will comprehensively introduce the research progress of above methods in the field of cerebral venous sinus hemodynamics, and provide innovative solutions for subsequent research of cerebral venous system diseases.